2023
DOI: 10.2147/ndt.s399378
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12, Folate, Homocysteine, Inflammatory Mediators (Interleukin-6, Tumor Necrosis Factor-α and C-Reactive Protein) Levels in Adolescents with Anxiety or Depressive Symptoms

Abstract: Purpose To evaluate the prevalence of abnormal vitamin B12, folate, total homocysteine (tHcy), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), C-reactive protein (CRP) levels, to analyze the relationship between these parameters and the severity of anxiety or depressive symptoms, and to explore the possible factors associated with abnormal levels of these parameters in adolescents with anxiety or depressive symptoms. Methods Adolescent (aged 12–18 years) outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…In this study, the severity of depression and anxiety were correlated with vitamin B12, folate and Hcy, albeit weakly (Tan et al 2023). In addition, it was found that taking more B vitamins with diet during adolescence is associated with lower depressive symptoms (Murakami et al 2010).…”
Section: Introductionmentioning
confidence: 47%
“…In this study, the severity of depression and anxiety were correlated with vitamin B12, folate and Hcy, albeit weakly (Tan et al 2023). In addition, it was found that taking more B vitamins with diet during adolescence is associated with lower depressive symptoms (Murakami et al 2010).…”
Section: Introductionmentioning
confidence: 47%
“…This association between vitamin B 12 deficiency and greater severity of GAD, as shown by the present study, is consistent with the findings of several studies. In fact, a recent Chinese study [22] that has been conducted using the same scale as the one used in our study (GAD-7 scale), found that lower serum levels of vitamin B 12 were associated with greater risk of severe anxiety. However, a cross-sectional study conducted in India [23] found no direct correlation between vitamin B 12 deficiency and GAD, but a considerable higher risk of developing GAD in individuals with hyperhomocysteinemia.…”
Section: Phq-9 Gad-7 and Isi Total Scores According To Vitamin B 12 L...mentioning
confidence: 59%
“…Although this study demonstrated that low serum levels of vitamin B 12 were associated with increased severity of insomnia, our results do not match with the findings of other studies. A study conducted in 2019 [ 22 ] found that vitamin B 12 levels did not significantly affect the severity of insomnia. Furthermore, it is of particular interest to mention than another study [ 24 ] found that vitamin B 12 levels were considerably higher in insomniac individuals, which does not correlate with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…S-adenosylmethionine helps in the methylation of neurons in the brain which imparts the antidepressant effect (7) . Vitamin B12 deficiency and to a lesser extent folate deficiency were also related to depressive disorders (8) . Synthesis of monoamines (dopamine and serotonin) is dependent on both folate and vitamin B12.…”
Section: Introductionmentioning
confidence: 99%